Bazooka/PAR3 is dispensable for polarity in Drosophila follicular epithelial cells - Shahab, Jaffer (Biol Open, 2015)
Apico-basal polarity is the defining characteristic of epithelial cells. In Drosophila, apical membrane identity is established and regulated through interactions between the highly conserved Par complex (Bazooka/Par3, atypical protein kinase C and Par6), and the Crumbs complex (Crumbs, Stardust and PATJ). It has been proposed that Bazooka operates at the top of a genetic hierarchy in the establishment and maintenance of apico-basal polarity. However, there is still ambiguity over the correct sequence of events and cross-talk with other pathways during this process. In this study, we reassess this issue by comparing the phenotypes of the commonly used baz(4) and baz(815-8) alleles with those of the so far uncharacterized baz(XR11) and baz(EH747) null alleles in different Drosophila epithelia. While all these baz alleles display identical phenotypes during embryonic epithelial development, we observe strong discrepancies in the severity and penetrance of polarity defects in the follicular epithelium: polarity is mostly normal in baz(EH747) and baz(XR11) while baz(4) and baz(815)(-8) show loss of polarity, severe multilayering and loss of epithelial integrity throughout the clones. Further analysis reveals that the chromosomes carrying the baz(4) and baz(815-8) alleles may contain additional mutations that enhance the true baz loss-of-function phenotype in the follicular epithelium. This study clearly shows that Baz is dispensable for the regulation of polarity in the follicular epithelium, and that the requirement for key regulators of cell polarity is highly dependent on developmental context and cell type.